O emprego da informática na trajetória acadêmica dos alunos de licenciatura do Centro de Educação da UFSM - Bocca, Márcia Bianchi da Silva (2004)
The following research investigates the use of computation during the academic life of students enrolled in the undegraduate courses of education and special education at the School of Education, Federal University of Santa Maria. Its main goal was to analyse the wishes and hopes expressed by those students about the use of computation. In order to attain the above mentioned target we tried to understand the reasons which were driving students to use the resources of the School of Education Computation Laboratory (LINCE). By so doing we would know which applications and Internet tools students most utilize during their academic course. In the sequence we tried to identify the possible influences computation may exert in the future student's professional life in order to verify how they are searching for knowledge through the Internet. In this way the investigation can be labeled as a descriptive study with qualitative approach, of phenomenologic nature, and being typified as a case study. This methodologic proposal turned it possible for us to participate, undestand and interpret the attitudes and the activities developed by students at the Computation Lab. Took part of the present research six pupils of the sixth, seventh and eighth semesters of the undergaduate courses located at the School of Education. It was verified that all of them have very poor experiences respecting computing resources but even though these are enough to supply their academic needs, such as processing texts and do searchs through the Internet. Thus it was possible to ascertain, throughout the research, that students have a significant interest in exploring the technical resources of computation at their disposal in the Computation Lab but ignore the literature about this subject. At the same time they show a striking hope to insert these instruments in classroom work, even if they are conscious of not being ready to develop activities together with their future pupils at the schools computation laboratories. Given this reality, it is necessary to change curricula of teachers' educating courses in their own structure: a change that gives a new definition to the role of a teacher facing computing resources and helps in driving the teaching-learning process to emphasize the use of computers within the school environment. We believe that this lack lived by students of licensing courses during their academic life does not have its sources in the pure utilization of a technical resource but in actions not preceded by the necessary discussion of all the community of the School of Education about limits and possibilities for education of information technology